Penguatan Literasi Siswa Sekolah Dasar melalui Program KKN Institut Madani Nusantara di Desa Buniwangi Kecamatan Gegerbitung: Penelitian - Linda Hindriana; Azmi Abdulhakim; Wildan Khoir Lubis; Raihan Naufal Lisaputra; Maria Ulfa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Buniwangi Village, Gegerbitung Subdistrict, Sukabumi Regency, still struggles with low basic literacy among school students. Many children are not fluent in reading Latin script despite being able to read the Qur’an. This condition is influenced by limited learning facilities, lack of reading materials, and teacher-centered methods. Through the Community Service Program (KKN) of Institut Madani Nusantara, students promoted literacy by organizing shared reading activities, introducing and simulating the National Assessment (ANBK), and integrating religious readings with Latin texts. The program received positive responses from both students and teachers and encouraged community involvement in supporting children’s literacy. As a result, awareness of literacy’s importance increased, providing an initial step toward strengthening a reading culture in Buniwangi Village..